Food policy integrating health, environment and society - Lang, Tim.; Barling, David; Caraher, Martin (Oxford : Oxford University Press, 2009)
Food policy has long been viewed as an essential part of the public health agenda, but this book identifies the importance of environmental damage and social inequalities to these issues. The authors offer a review of current and past food policy, proposing the need for a new ecological public health approach to food policy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nutrition policy -- Great Britain; Public health -- Great Britain